(untitled) (Research, Society and Development, 2022)
The relevance exercised by educators in all stages of the students’ learning process is notorious. However, contemporaneity has brought several challenges, such as technological advancement, socioeconomic and cultural issues, among others. Thus, it is necessary new practices and strategies that help in the pedagogical didactic work. In order to contribute to the educational practice of Mathematics educators, the objective of this work is to bring theoretical and practical reflections on the use of games as a teaching method, where students not only experience situations that are repeated, but learn to deal with them. symbols and doing analyses. It is a research with a qualitative approach, of the bibliographic type. For data collection, the documentary corpus was researched in articles, books, documents, such as the National Common Curricular Base (BNCC) and D’Ambrósio, 1996.